1998
DOI: 10.1038/sj.sc.3100591
|View full text |Cite
|
Sign up to set email alerts
|

Lateral approach of the dog brachial plexus for ventral root reimplantation

Abstract: A lateral surgical approach of the cervical spinal cord and brachial plexus was developed in nine dogs for avulsion and reimplantation of the ventral cervical spinal roots (C). The surgical steps involved in exposing the spinal cord and roots are described. The avulsed rootlets of C6 and C7 were reimplanted in their initial position. As a direct consequence of the avulsion, accid paralysis of the shoulder and severe amyotrophy developed within 5 ± 7 weeks on the injured side. In addition, the dogs exhibited cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…From their location in lamina IX and their morphology, most of the labelled neurons appeared to be motoneurons. These findings are in full agreement with previous experiments carried out in adult dogs and monkeys (Moissonnier et al ., 1998; Hallin et al ., 1999). In the present study, the original stem axon was completely severed in the avulsion.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…From their location in lamina IX and their morphology, most of the labelled neurons appeared to be motoneurons. These findings are in full agreement with previous experiments carried out in adult dogs and monkeys (Moissonnier et al ., 1998; Hallin et al ., 1999). In the present study, the original stem axon was completely severed in the avulsion.…”
Section: Discussionsupporting
confidence: 94%
“…It has also been suggested that axons sprout as collateral branches from motoneurons in adjacent segments (C7 and T1 in our case). In studies using dogs and rats (Bertelli & Mira, 1994; Moissonnier et al ., 1998), most labelled spinal neurons were concentrated in the segment of ventral root or peripheral nerve graft reimplantation, although a few were observed both in the rostral and in the caudal segments, suggesting axonal sprouting of long collateral branches coursing in the grey matter. In our reimplanted animals, however, only a few motoneurons were labelled in C7 and T1, whereas large numbers were labelled in C8.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported that rootlet reimplantation into the spinal cord in people can promote motor reinnervation of denervated muscles . In the dog, this potential surgical therapy for brachial plexus injuries has unsatisfactory results because of the large distance of neurotization from the spinal cord to the muscular effector, and because of the low number of motor neurons that can regenerate through the reimplanted rootlets . Rootlet reimplantation has not been widely used in clinical cases by veterinary surgeons for multiple reasons: the need for weight bearing in dogs (which is not the case in people); signs of reinervation take many months during which continuous postoperative care is necessary; and the relatively good quality of life after forelimb amputation in dogs…”
Section: Introductionmentioning
confidence: 99%
“…Given this morphological evidence, reasonable functional recovery appears likely. Nevertheless, little is known about variations in the branching pattern of the brachial plexus in dogs, excluding some reports in which the authors referred only to surgical approaches to the brachial plexus [11,16,17]. This knowledge is required to maximize the chances of successful grafting operations.…”
mentioning
confidence: 99%